O TESTEMUNHO DE MULHERES NO MUSEU DO HOLOCAUSTO: MEMÓRIA E DISCURSIVIDADE - Ferreira, Scarlaty Horrarah (2021)
The research falls within the theoretical scope of Discourse Analysis derived mainly from Michel Pêcheux and Eni Orlandi. We present in the analyses the relations between discourse, memory and history, produced by the testimonies of women in the Holocaust Museum of Curitiba. We signify this museum as a "place of memory" which presentifies the past and institutionalizes social, cultural and historical memories. The analytical cut focuses on the exhibition "Entre Aspas", from the testimonies exhibited at the Holocaust Museum, giving special emphasis to the conditions of discourse production, understanding that these are testimonies of Jewish women who survived and came to live in Brazil. We put in suspension the sense effects about survivors, about the Holocaust and about the importance of life, which constitute sense effects of memories of death that make the subjects stronger. The research question we seek to answer, in this dissertation, is: How is the discourse of/about Holocaust survivors engendered from witnesses and their testimonies in the construction of (dis)ongoing memories, reinforcing the representation of survivors and their practices of resistance to the genocide and barbarities of the III Reich? And how do these testimonies legitimize/anchor Curitiba's Holocaust Museum as a place of memory of the Shoah? We conclude that the discourses of Holocaust survivors are engendered from witnesses who contribute to the construction of Holocaust memories and reinforce the meanings around survivors, establishing a positive imaginary. Moreover, the testimonies legitimize/anchor Curitiba's Holocaust Museum as a place of memory of the Shoah, by inscribing these memories in the symbolic. In this memorial space, previously said meanings return, filed and organized by means of testimonies so that they discursively function constituting effects, within an ideological direction. The witnesses are presented in an idealized and heroic way. The testimonial discourses inscribe the repeatable and give visibility to regularities of the functioning of a place of memory that is not artificial, nor natural, nor does it arise from chance, but from the desire of "making memory" (VENTURINI, 2009).